Research Handbook on Property, Law and Theory - Bevan, Chris (Northampton : Edward Elgar Publishing, 2024)
"This comprehensive Research Handbook interrogates and offers historical as well as contemporary understandings of property, property law and property theory. Chapters locate the role of property in key theoretical debates and examine property's place in significant social contexts, covering topics such as Indigenous property, artificial intelligence, cryptoassets, property and the art world, environmentalism and climate change. Bringing together over 30 contributors from Asia, Australasia, Europe, and North America, the Research Handbook surveys the dynamic fields of property and property law across legal traditions through different historical, contemporary, comparative and jurisdiction-specific lenses. Contributing authors pose questions as to how property can and should be theorised and conceptualised, incorporating insights from feminist and LGBTQ+ perspectives, as well as questions surrounding property and emotion, squatting and human rights issues. Contributors explore how property operates in different legal frameworks and in these distinct contexts, reflecting on property's place in theory and society. Presenting unique insights from leading experts in the field, this prescient Research Handbook is a thought-provoking read for students and scholars of legal theory, property law, property theory and socio-legal studies"--
Includes bibliographical references and index.
Keywords: Property; Right of property; Property -- Philosophy